Analisis Sikap Sosial Mahasiswa melalui Self-Assessment Berbasis Level Afektif pada Mahasiswa PGMI Semester IV - Muthia Salsabila; Elghin Chelsea Al-ghistni; Desnina Eva Amelia; Aliya Sayida; Asep Ediana Latip (LP2M STIT Palapa Nusantara, 2026)
The limited use of affective level-based self-assessment in assessing students’ social attitudes indicates the need for a more reflective, participatory, and relevant evaluation approach for developing the character of prospective educators. This study aims to analyze the social attitudes of fourth-semester PGMI students through self-assessment focused on the aspects of cooperation, empathy, tolerance, communication, mutual cooperation, and respect. This study used a descriptive quantitative approach with purposive sampling involving 32 fourth-semester PGMI students. Data were collected through an affective level-based self-assessment questionnaire and then analyzed using descriptive quantitative analysis based on the mean score for each indicator. The results showed that students’ social attitudes were in the high category across all aspects analyzed. The tolerance aspect obtained the highest percentage of 96.9%, whereas the aspects of cooperation, mutual cooperation, and respect each reached 90.6%. The aspects of empathy and communication skills were at 87.5%. These findings indicate that affective level-based self-assessment functions not only as an evaluation tool but also as a means of reflection that helps students understand and develop social attitudes gradually through the affective levels of receiving, responding, valuing, organizing, and characterizing. The conclusion of this study emphasizes that affective level-based self-assessment can be used as a reflective and participatory evaluation approach in measuring the social attitudes of PGMI students. The implications of this study provide a contribution to the development of affective evaluation in higher education and serve as a basis for designing a more innovative attitude assessment model that is responsive to the needs of 21st-century learning.